A Child Education Model in an Effort to Improve the Culture of Healthy Snacks and Breakfast Based on Parents and Children at SDN 04 Kampung Olo, Padang City - Dewi Murni; Susmiati; Rika Fatmadona; Aurel Az-zahra Beslia; Afifah Mardiah; Lutfianti Fafauziah; Zahira Assyfa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
Unhealthy breakfast and snack habits are still common among school-aged children and can lead to decreased concentration, weakened immunity, and poor digestion. This education-based program aims to increase students' and parents' knowledge and awareness regarding nutritious breakfasts and the selection of safe and healthy snacks. This activity was carried out at SDN 04 Kampung Olo, Padang, involving students, parents, and teachers. Activities included interactive nutrition education, guided breakfast sessions, demonstrations on identifying healthy snacks, and knowledge assessments using ore-post-tests. The results showed an increase in knowledge with the average student score increasing from 31.7 to 32.6 and the parent score from 29.6 to 30.4. Positive behavioral changes were also observed, including more consistent breakfast consumption, a better understanding of the criteria for healthy snacks, increased hand washing practices before eating, and an increase in parents' ability to prepare balanced meals and support healthy eating habits at home. These results indicate that school- and family-based nutrition education can effectively strengthen knowledge and encourage healthier dietary behaviors. Ongoing collaboration between schools, families, and health professionals is recommended to encourage long-term healthy eating habits and improve the well-being of school-aged children.